Identification of low gamma-glutamyl transferase familial intrahepatic cholestasis - benign recurrent intrahepatic cholestasis in a 22-year-old woman: A case report and literature review - Kamińska, Marta; Klapaczyński, Jakub; Ołdakowska-Jedynak, Urszula; Kamińska, Dorota (Kwartalnik Naukowy Fides et Ratio, 2022)
Introduction: Benign recurrent intrahepatic cholestasis (BRIC) is a rare genetic disorder characterized by recurrent episodes of cholestatic jaundice that may last days to months. It can start at any age, but often in a first decade of life. The syndrome does not lead to progressive liver dysfunction and cirrhosis. Between cholestatic episodes patients have no symptoms and laboratory levels are within the norms. The exact mechanism of cholestasis in BRIC and many other cholestatic conditions is poorly understood. Syndrome the first time was described in 1959r., in 2004 was proposed the following diagnostic criteria. The report presents a 22-year-old woman with the diagnosis of jaundice with an accompanying severe pruritus (first episode of BRIC).The aim: This article describes clinical presentation, laboratory abnormalities, and proposed etiologic factors responsible for BRIC. We intend to report this case due to rarity of this disease in Poland.Clinical case: Described as a clinical case course features of the BRIC. Knowledge of this entity is important issue as an early recognition that might prevent performance of expensive diagnostic algorithm. The laboratory tests and the whole clinical picture had conclusive results. Moreover, despite negative genetic test, the authors were sure that it is BRIC.Conclusion: BRIC is a disease not leading to progressive liver dysfunction and cirrhosis. It should be remembered the characteristic symptoms of BRIC, a very low level of GGT accompanied by jaundice and itching. It has a great diagnostic importance (by shortening the procedure algorithm), allowing for a quick diagnosis.